1964
DOI: 10.1530/acta.0.0450329
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Gonadotrophin From Menopausal Urine by Gel Filtration on Sephadex

Abstract: The further purification of HMG obtained from postmenopausal urine with kaolin-acetone, DEAE-C and permutit chromatography was performed using gel filtration on Sephadex (G 200). The potency of the purest fraction isolated was about 2.5 times higher than that of the starting material. The total recovery of biological activity was 96 %.Several methods using ion-exchange materials for the purification of human pituitary gonadotrophin (HPG) and human menopausal gonadotrophin (HMG) have been proposed.The chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Large pools of pituitaries had been collected at autopsy in hospitals, mainly from elderly men and women. A few years later, Donini et al reported a method for the extraction of gonadotrophins from human menopausal urine, and these extracts, called human menopausal gonadotrophins (hMG), were soon introduced for ovulation induction (2). Two decades later, highly purified FSH isolated from menopausal urine was marketed for ovulation induction (3).…”
Section: Introductionmentioning
confidence: 99%
“…Large pools of pituitaries had been collected at autopsy in hospitals, mainly from elderly men and women. A few years later, Donini et al reported a method for the extraction of gonadotrophins from human menopausal urine, and these extracts, called human menopausal gonadotrophins (hMG), were soon introduced for ovulation induction (2). Two decades later, highly purified FSH isolated from menopausal urine was marketed for ovulation induction (3).…”
Section: Introductionmentioning
confidence: 99%
“…In 1964 Donini reported the extraction of human gonadotropins (HMG) from human menopausal urine in sufficient quantities; and later introduced the use of HMG for ovarian stimulation as a treatment for amenorrhea ( 6 ). In these studies, he identified forms of hyperstimulation and described the untoward side effect of multiple pregnancies as a result of the use of HMG and hCG for ovulation induction.…”
Section: Isolation and Purification Of Gonadotropinsmentioning
confidence: 99%
“…As a result, pituitary FSH and LH secretion is no longer inhibited and high serum levels and increased urinary excretion ensues. Donini et al (1964) described techniques to extract these hormones from the urine of menopausal women for biologic use in women of reproductive age. The first preparation of human menopausal gonadotropins (hMG) for clinical use was released in 1950 (Table 1).…”
Section: Urinary Extracts Of Gonadotropinsmentioning
confidence: 99%